PERAN LEMBAGA AMIL ZAKAT, INFAK dan SEDEKAH MUHAMMADIYAH (LAZISMU) DALAM PEMBERDAYAAN EKONOMI MUSTAHIK PERIODE 2016-2018 - WAHIDIN MUSTA’IN BILLAH; MUFID HABIB MUSTOFA; KHALIMI KHALIMI (Institut Bisnis Muhammadiyah Bekasi, 2020)
Empowerment is a standard of living that is desidered for all people, especially those in the middle to lower category or commonly known as the poor. One of the zakat collecting, Management, and Collection Institutions that has tried to deal with poverty is the Mustahik economic empowerment program implemented by one of the programs called the establishment of 1000 MSME (Micro Small and Medium Enterprises) under the auspices of the Muhammadiyah central board of Muhammadiyah. Mustahik economy after the program. This research focuses on one problem, namely: what are the supporting and inhibiting factors of LAZISMU Muhammadiyah central leadership in the implementation and improvement of the mustahik economy. This type of research is a qualitative study, while the specifications of this study are based on observations, interviews and documentation obtained when conducting activities in the field (field research). The result of this study are first, an increase in house should income, second, an increase in the accumulation mustahiq 1000 MSME Programs, including:first, Strengthening the characters of business, training and motivation to trade, second, guidance and assistance in running the Micro, Small, and Medium Enterprises. Supporting factors in the implementation and improvement of the mustahik economy is that there is a clear guideline concept on employee loyalty, very high companion program loyalty and capital and donors available so that the program can run. While the inhibiting factors are limited capital from available zakat funds, uneven level of education among MSME members, difficulty in finding donors because LAZISMU Muhammadiyah central leadership is not in accordance with the program that is expected of donors, there is no responsibility from mustahiq members and there are financial reports lack of openness (transparency) regarding fund management which explains the source of funds collected and some funds channeled.